THE RELATIONSHIP BETWEEN EARLY MARRIAGE AND DIVORCE RATES FROM THE PERSPECTIVE OF ISLAMIC EDUCATION - Hadi, Rusniyanti; Ridwan, Muhammad; Rusli (Lembaga Penelitian dan Pengabdian Masyarakat FKIP UMB, 2024)
Early marriage remains a common phenomenon in various regions, including Kelurahan Lipu, Baubau City. This practice is often influenced by cultural norms, social pressure, and limited understanding of Islamic values regarding marriage. In fact, marriage is a sacred bond that requires psychological, spiritual, and social readiness. This study aims to examine the relationship between early marriage and divorce rates from the perspective of Islamic education. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, observations, and documentation using a saturated sampling technique involving young married couples, religious leaders, and community figures. The findings reveal a strong correlation between early marriage and the high rate of divorce. Contributing factors include the dominance of social norms, a lack of understanding of Islamic marital principles, and the absence of premarital guidance rooted in religious teachings. These results underscore the importance of comprehensive premarital education and the active role of religious institutions in preparing young couples to build a harmonious family life based on Islamic values.